KOMUNIKASI KESEHATAN BERBASIS HEALTH BELIEF MODEL: INTENSI KONSUMSI TABLET TAMBAH DARAH PADA SISWI - Seminar, Annisa Utami; Sarwoprasodjo, Sarwititi; Khomsan, Ali; Alfiani, Diana; Sianturi, Sephia Ellyana (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The IFA (Iron Folic Acid) Supplements program among schoolgirls is one of the specific interventions from the Ministry of Health in Indonesia to overcome the high stunting rate in Indonesia. However, several studies found that there are still few female students who want to take IFA. This study aims to analyze intention of female students in taking IFA based on health belief model and emphasize the cues to action construct as a health communication variable in this model. The research was conducted through a survey of 92 female students from two schools in Dramaga District and Ciampea District, Bogor Regency using a quantitative approach. The PLS-SEM application is used to analyze the relationship between variables and test hypotheses. This research found that knowledge and source of information and cues to action influence intention to consume TTD. The results of this research can contribute to improving TTD program interventions that strengthen cues to action or various health communication means regarding IFA to female students.